Significant structural change in human c-Myc promoter G-quadruplex upon peptide binding in potassium. Issue 13 (8th March 2022) - Kundu, Nikita; Sharma, Taniya; Kaur, Sarvpreet; Singh, Mamta; Kumar, Vinit; Sharma, Uttam; Jain, Aklank; Shankaraswamy, Jadala; Miyoshi, Daisuke; Saxena, Sarika
Abstract : We selected the G-quadruplex motif located in the nuclease-hypersensitive elements (NHE) III1 region of the c-Myc promoter and for the first time performed its interaction studies with a designed peptide (QW10). Abstract : We selected the G-quadruplex motif located in the nuclease-hypersensitive elements (NHE) III1 region of the c-Myc promoter and for the first time performed its interaction studies with a designed peptide (QW10). Our CD results showed that the peptide bound to the c-Myc G-quadruplex and induced a significant blue shift in the positive peak of 20 nm in KCl alone or with 40wt% PEG200 or 20wt% PEG8000 in comparison to NaCl. Our Native Gel results confirmed that peptide binding destabilized the duplex and stabilized the unimolecular G-quadruplex and not binding to i-motif. UV thermal results confirmed destabilization of bimolecular structure and stabilization of unimolecular G-quadruplex. QW10 showed preferential binding towards c-MYC promoter G4 with binding constant ( K b ) values of the order of 0.05 ± 0.2 μM, 0.12 ± 0.1 μM and 0.05 ± 0.3 μM for complexes in K + alone or 40wt% PEG 200 or 20wt% PEG 8000 respectively. QW10 showed preferential cytotoxicity with IC50 values of 11.10 μM and 6.44 μM after 72 and 96 hours' incubation on Human Breast Carcinoma MDA-MB 231 cells and was found to be non-toxic with Human Embryonic Kidney (HEK-1) cells. Interestingly, we observed reduction of c-Myc gene expression by 2.5 fold due to QW10 binding and stabilizing c-MYC G4. Our study for the first time provides an expanded overview of significant structural change in human c-Myc promoter G-quadruplex upon peptide binding in potassium.